2022
DOI: 10.4103/ijem.ijem_334_22
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Clinical Profile of Maturity Onset Diabetes of the Young among People with Diabetes Attending a Tertiary Care Centre

Abstract: Background: Maturity onset diabetes of young (MODY) is considered to be the most underdiagnosed condition. The correct diagnosis of MODY has a definite bearing on the outcome and clinical course of the disease. We aim to determine the prevalence and clinical profile of MODY among young diabetic patients attending at Department of Endocrinology, a tertiary care institute in North India. Methods: It was a cross-sectional study involving all consecutive co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
0
0
Order By: Relevance
“…In the current study 10% had neuropathy, none of cases had acanthosis nigricans, or lipodystrophy. This was comparable with Bhat et al, (22), who reported that a considerable number of MODY patients in their study were found to have microvascular complications. Diabetic peripheral neuropathy was the most frequent complication observed in 14% of patients which was unrelated to duration of DM.…”
Section: Resultssupporting
confidence: 91%
“…In the current study 10% had neuropathy, none of cases had acanthosis nigricans, or lipodystrophy. This was comparable with Bhat et al, (22), who reported that a considerable number of MODY patients in their study were found to have microvascular complications. Diabetic peripheral neuropathy was the most frequent complication observed in 14% of patients which was unrelated to duration of DM.…”
Section: Resultssupporting
confidence: 91%